Ulasan Matakuliah Elektif Art Collaborative: Desain dan Evaluasi Matakuliah Elektif pada Jurusan Bisnis Universitas Prasetiya Mulya - da Silva, Novira (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2019)
Creative economy acts as economic activator and the activities has been growing in the last years. The activities focused on creative ideas. Arts and the related media can be used to enhance creativity. Business Undegraduate program in Prasetiya Mulya University addressing this issue by opening elective course Art Collaborative. This study use qualitative descriptive method and has a purpose to explain the design of the course and to give evaluation for the course. The course is conducted on 2018-2019 academic year. The findings are students have additional knowledge with the combination method of lecturing and workshop during the course. Topics given are also in line with students’ expectation. Evaluation for this course are extending the allocated time for workshop and providing variety of topics. Other important findings are most students expect this course to be continued in the next semester.